Waralaba (Franchise) di Indonesia (Lex Jurnalica, 2011)
Franchise contracts are granting permission by the holders of Intellectual Property Rights or other know-how to other parties to use the brand or a particular procedure is and as kopensasinya franchise holder shall pay a royalty for use of trademarks and product manufacturing processes that amount to be determined in the form of a written agreement bardasarkan , where in the event of cancellation of the agreement, then the franchise to Demand acquisition compensation and the fulfillment of the agreement.Keywords: Franchise, Agreement, Royalty